2001
DOI: 10.3168/jds.s0022-0302(01)74660-7
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Binding by Dairy Strains of Lactic Acid Bacteria and Bifidobacteria

Abstract: Various food commodities including dairy products may be contaminated with aflatoxins, which, even in small quantities, have detrimental effects on human and animal health. Several microorganisms have been reported to bind or degrade aflatoxins in foods and feeds. This study assessed the binding of aflatoxin B1 (AFB1) from contaminated solution by 20 strains of lactic acid bacteria and bifidobacteria. The selected strains are used in the food industry and comprised 12 Lactobacillus, five Bifidobacterium, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
225
4
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(255 citation statements)
references
References 13 publications
19
225
4
7
Order By: Relevance
“…Another possible explanation associated with this observation is that the effect of fermentation process generally employed in the processing of cassava into dried cassava, cassava flour, and ubuswage favors the growth of lactic acid bacteria (LAB) or some microorganisms like Saccharomyces cerevisiae strains. The ability of these microorganisms to bind or degrade aflatoxins, especially aflatoxin‐B 1 and aflatoxin‐M 1 , in foods and feeds has been reported (Ahlberg, Joutsjoki, & Korhonen, 2015; El‐Nezami & Gratz, 2011; Peltonen, El‐Nezami, Haskard, Ahokas, & Salminen, 2001). Aflatoxin binding seems to be strongly related to several factors such as LAB strains, matrix, temperature, pH, and incubation time (El‐Nezami & Gratz, 2011; Shetty, Hald, & Jespersen, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation associated with this observation is that the effect of fermentation process generally employed in the processing of cassava into dried cassava, cassava flour, and ubuswage favors the growth of lactic acid bacteria (LAB) or some microorganisms like Saccharomyces cerevisiae strains. The ability of these microorganisms to bind or degrade aflatoxins, especially aflatoxin‐B 1 and aflatoxin‐M 1 , in foods and feeds has been reported (Ahlberg, Joutsjoki, & Korhonen, 2015; El‐Nezami & Gratz, 2011; Peltonen, El‐Nezami, Haskard, Ahokas, & Salminen, 2001). Aflatoxin binding seems to be strongly related to several factors such as LAB strains, matrix, temperature, pH, and incubation time (El‐Nezami & Gratz, 2011; Shetty, Hald, & Jespersen, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Rahaie et al (2012) observed that heat treated cells of L. rhamnosus GG could adsorb 85% of AFB 1 (10 ng/ml) from the medium. Peltonen et al (2001) also studied viable cells of L. rhamnosus (strains E-97800, LC 1/3 and CSCC 2420) and found AFB 1 binding percentages of 22.7%, 54.6% and 33.1%, respectively. It can observed that within a genus or even within a determined species, not all strains are equivalent in terms of toxin removal, on the contrary, aflatoxin binding capacity is a characteristic of only specific strains, and its effectiveness varies markedly (El-Nezami et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen different types of aflatoxins have been identified so far, and aflatoxin B 1 (AFB 1 ) is the most prevalent and toxic metabolite produced by the fungi (Bhat et al, 2010). Several studies have demonstrated the efficiency of different species and strains of LAB in adsorbing aflatoxins from contaminated media (El-Nezami et al, 1998;Pierides et al, 2000;Oatley et al, 2000;Haskard et al, 2001;Peltonen et al, 2001;Azab et al, 2005;Fazeli et al, 2009;Bovo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the authors have not discussed, the difference observed between the inhibitory effect in the presence and absence of the LAB cells could be attributed to a binding or sequestration effect caused by the LAB cells. Binding of mycotoxins by LAB has been well documented in the literature (53,54,55,56,57).…”
Section: Inhibition Of Mycotoxin Productionmentioning
confidence: 99%
“…Treating these strains with 1M HCl significantly enhanced their ability to remove aflatoxin (59). While screening dairy strains (LAB and bifidobacteria) for their ability to bind aflatoxin B 1 , Peltonen et al (54) found that between 5 and 60% of the aflatoxin in solution was bound by the bacteria, with L. amylovorus and L. rhamnosus being the most efficient species.…”
Section: Mycotoxin Bindingmentioning
confidence: 99%